PKM PANTI ASUHAN AS-SALAM â€œOPTIMALISASI KESEHATAN REPRODUKSI REMAJA MELALUI PENDAMPINGAN JACARE (REMAJA CARE)â€ TAHUN 2021 - Dwi Sapta Aryantiningsih; Linda Suryani (Jurnal Pengabdian Masyarakat Multidisiplin, 2021)
Adolescent reproductive health is very important to pay attention to because the consequences are very broad. One of the consequences of the lack of attention to reproductive health by adolescents is that many adolescents are found to have infections in the reproductive organs, especially the genitals. Only 21.6% of adolescents carried out personal hygiene behavior correctly, and 28% of adolescents who received information about PIK-Remaja (Adolescent Information and Counseling Center) related to reproductive health. A teenager needs to get assistance in order to get the right information so that problems with sexual and reproductive health do not occur. Peer education will have an impact on increasing one's knowledge, attitudes and actions in maintaining personal hygiene. The purpose of this community service is so that problems around adolescent reproductive health can be resolved and there is a discussion room with peers known as adolescent care (Jacare) to discuss reproductive health problems. The method of implementing PKM activities in outline includes the stages of training, forming Jacare, mentoring and evaluation. After providing education and establishing Jacare as a forum for assistance for orphanage children and the mentoring process, a positive impact was obtained, namely an increase in the knowledge and skills of the As-Salam Orphanage children regarding reproductive health. Assistance activities carried out, made the children of the orphanage express the problems they were facing to Jacare so that the problems faced could be resolved. Therefore, it is necessary to provide ongoing assistance to orphanage children to overcome the problems they face.